Concept design and numerical evaluation of a highly efficient rotary electrocaloric refrigeration device. (25th May 2021) - Li, Qiang; Shi, Junye; Han, Donglin; Du, Feihong; Chen, Jiangping; Qian, Xiaoshi
Highlights: A rotary EC refrigeration device concept and its working principle are presented. The detailed operating strategy and system layout are displayed. Simulation results of cooling performances under three strategies are compared. Refrigeration capacity corresponding to different heat transfer fluid are revealed. Abstract: Enabled by the discovery of giant electrocaloric effect (ECE) in inorganic ceramics and organic polymers, Electrocaloric (EC) cooling technology has attracted considerable attention from both academia and industrial. However, there remains many challenges in the refrigeration efficiency and/or capacity of the currently reported electrocaloric refrigeration devices. In this work, we propose a concept design of EC refrigeration device, in which the working bodies are rotating in a plane perpendicular to the direction of fluid flow. The rotary EC device adopting heat transfer fluid as an intermediate medium allows for improved heat exchange between EC materials and outside environment, and efficiently delivers cooling effects to where it's needed. Simulations have been performed to investigate the system cooling performance under different operating strategies. Meanwhile, comparative researches on different heat transfer fluid are conducted and the corresponding cooling effects are studied. When using deionized water as heat transfer medium, the system can achieve a cooling power density of 9.89 W·cm −3 and COP of 10.48 over 10 K temperature span. In general, this work provides a highly-efficient rotary EC refrigeration device concept that employs fluid–solid conjugated heat transfer, and guides the optimization of operating strategy and selection of heat transfer fluid.